OPTIMASI PERAWATAN SISTEM PENDINGIN MESIN UTAMA TIPE MITSUBISHI 6UEC52LS PADA KAPAL PADA KAPAL MT. PRINCESS NAOMI - Wibowo, Waris; Astriawati, Ningrum; Primagani, Angga (Jurusan Teknik Mesin Fakultas Sains dan Teknik Universitas Bangka Belitung, 2025)
The purpose of the study is to optimize the cooling system maintenance on the Mitsubishi 6UEC52LS Main Engine on the MT. Princess Naomi belongs to PT. Waruna Nusa Sentana. This research was conducted in the engine room of the MT. Princess Naomi. This research employed qualitative descriptive approach methods. Data collection techniques were obtained through field research by combining observation methods, documentation, in-depth interviews, and a literature review. Data analysis was conducted in triangulation (combination). The results of the study showed that the maintenance of the diesel engine cooling system on the MT. Princess Naomi belongs to PT. Waruna Nusa Sentana has been running optimally with an average after optimization treatment of 83.75%. The cooling system on the main engine of the MT. Princess Naomi applied a closed cooling system. Parts of the cooling system treated include: expansion tank, centrifugal pump, fresh water cooler, sea chest